Resveratrol production from several types of saccharide sources by a recombinant Scheffersomyces stipitis strain - Yuma Kobayashi (Elsevier, 2021)
Resveratrol is a plant-derived aromatic compound with a wide range of beneficial properties including antioxidant and anti-aging effects. The resveratrol currently available on the market is predominantly extracted from certain plants such as grape and the Japanese knotweed Polygonum cuspidatum. Due to the unstable harvest of these plants and the low resveratrol purity obtained, it is necessary to develop a stable production process of high-purity resveratrol from inexpensive feedstocks. Here, we attempted to produce resveratrol from a wide range of sugars as carbon sources by a using the genetically-engineered yeast Scheffersomyces stipitis (formerly known as Pichia stipitis), which possesses a broad sugar utilization capacity. First, we constructed the resveratrol producing strain by introducing genes coding the essential enzymes for resveratrol biosynthesis [tyrosine ammonia-lyase 1 derived from Herpetosiphon aurantiacus (HaTAL1), 4-coumarate: CoA ligase 2 derived from Arabidopsis thaliana (At4CL2), and stilbene synthase 1 derived from Vitis vinifera (VvVST1)]. Subsequently, a feedback-insensitive allele of chorismate mutase was overexpressed in the constructed strain to improve resveratrol production. The constructed strain successfully produced resveratrol from a broad range of biomass-derived sugars [glucose, fructose, xylose, N-acetyl glucosamine (GlcNAc), galactose, cellobiose, maltose, and sucrose] in shake flask cultivation. Significant resveratrol titers were detected in cellobiose and sucrose fermentation (529.8 and 668.6 mg/L after 120 h fermentation, respectively), twice above the amount obtained with glucose (237.6 mg/L). Metabolomic analysis revealed an altered profile of the metabolites involved in the glycolysis and shikimate pathways, and also of cofactors and metabolites of energy metabolisms, depending on the substrate used. The levels of resveratrol precursors such as L-tyrosine increased in cellobiose and sucrose-grown cells. The results indicate that S. stipitis is an attractive microbial platform for resveratrol production from broad types of biomass-derived sugars and the selection of suitable substrates is crucial for improving resveratrol productivity of this yeast.